Efektivitas Bursa Kerja Pemerintah Dalam Pengurangan Pengangguran: Studi Empiris Menggunakan Data Indonesia Family Life Survey (IFLS) 5 - Beni Teguh Gunawan (Pusat Penelitian dan Pengembangan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2017)
The objectives of this paper is to examine the effectiveness of government job fair compared to private job fair and other conventional job search methods. The government through the Ministry of Manpower efforted to provide job search facilities through job market both online and offline. On the other hand the private sector also does the same thing with the profit oriented objective. From all the job search alternative, this paper will counterpart the most effective method to reduce the unemployment. Using the 5th Wave Survey of Indonesian Family Life (IFLS) job seeker opportunities for employment jobs of 0.778 or 77.8% when using the private job fair while the goverment job fair does not significantly affected to probability to get job. While the level of education is divided into three lower, medium, and high groups, it can be seen that the government job fair is not significant in all education groups, while private employment is significant in medium and high education groups. The private job fair user from the medium eduacation group have probability to get job 0,789 or 78,9%, while the high education group have 0,91 or 91%.